Effect of ATNR (Asymetrical Tonic Neck Reflexs) Primitive Reflexs on Postural Control and Focus of Children Aged 5-8 Years at the Touch Care Mataram Physiotherapy Clinic - Muji Murtiningsih; Yuly Peristiowati; Agusta Dian Ellina; Nurwijayanti; Ratna Wardani (Journal Of Nursing Practice, 2025)
Background: Primitive reflexes affect emotional development, because in a healthy and well-developed brain, the baby will slowly integrate primitive reflexes naturally into a mature developed reflex pattern. In early childhood, children have begun to enter early childhood education, and the occurrence of postural disorders can occur due to the use of the wrong backpack, various types of movement behavior, physical activity and sports including genetic factors. Purpose: Analyze the effect of ATNR primitive reflex on postural control and focus of children aged 5-8 years at Touch Care physiotherapy clinic. Methods: Quantitative design with a cross sectional approach. This study was conducted at the Touchcare Mataram Physiotherapy clinic with a population of children aged 5-8 years who came to the TouchCare physiotherapy clinic to examine / consult. Sample determination using purposive sampling with the results of 102 children. Results: The results of the study based on hypothesis testing were 0.011 for postural control, which means that there is an effect of ATNR primitive reflexes on postural control in children aged 5-8 years. The focus variable has a significance level of 0.647, which means that the ATNR variable has no effect on the focus of children aged 5-8 years. The posture variable has a significance level of 0.155, which means that the ATNR primitive reflex variable has no effect on the posture of children aged 5-8 years. Conclusion: There is an influence between ATNR primitive reflex with postural control, posture and focus of children aged 5-8 years at Touchcare Mataram Physiotherapy clinic.